Exploring Student Perspectives on EFL Teachers’ Instructional Approaches and Classroom Management Strategies in Indonesian Secondary Schools - Rahmaeni, Rahmaeni (Universitas Muhammadiyah Enrekang, 2023)
The primary objective of this research was to investigate students' perceptions of EFL teachers' teaching methods and classroom management within the context of classroom interaction. Employing a descriptive quantitative approach, the study was conducted among students enrolled in SMP Darul Arqam Muhammadiyah Cece during the academic year 2022-2023, encompassing three classes. The sample selection utilized a purposive random sampling technique, with a focus on third-grade students, ultimately comprising a sample size of 20 students. Data collection involved a combination of observation and questionnaire administration. Upon applying the Likert scale to analyze students' perceptions of teachers' teaching methods and classroom management in English classes, the resultant data exhibited a mean score of 67.3%. This score signified a high level of agreement among students, indicating their positive reception of the employed teaching methods and classroom management strategies in the EFL classroom interaction. The research findings underscore the critical significance of teaching methods and classroom management in the broader context of the teaching and learning process. The study emphasizes the substantial impact that these factors wield in fostering students' developmental progress within the realm of learning English as a foreign language. In conclusion, the research illuminates the pivotal role of teaching methods and classroom management in the EFL classroom interaction through the lens of students' perceptions. The observed high level of agreement among students underscores the significance of these factors in shaping an effective educational experience. This study accentuates the profound influence of adept teaching methods and adept classroom management on students' English language acquisition and underscores the integral role they play in the broader educational landscape.